2022
DOI: 10.1371/journal.pone.0266477
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria and associated factors among symptomatic pregnant women attending antenatal care at three health centers in north-west Ethiopia

Abstract: Background Malaria is the disease caused by Plasmodium species and primarily transmitted by the bite of female Anopheles mosquitoes. During pregnancy, malaria causes life threatening outcomes to the mother, the fetus and the new born. Even though, malaria symptomatic pregnant women highly attract mosquitoes and have higher potential of transmitting the disease in communities, most of the previous studies focused on pregnant women with asymptomatic Plasmodium infections. Therefore, the aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
7
9
1
Order By: Relevance
“…In this study, adolescent pregnant women were found to have a higher prevalence of malaria infection with up to a twofold increase. This is in line with studies conducted in different sub-Saharan African countries which reported that young pregnant women are at the greatest risk of malaria infection and have the highest parasite densities [ 18 , 38 , 39 ]. This may be attributed to the fact that adolescent pregnant women did not have adequate exposure to health services and did not gain a good awareness about malaria and its prevention approaches.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, adolescent pregnant women were found to have a higher prevalence of malaria infection with up to a twofold increase. This is in line with studies conducted in different sub-Saharan African countries which reported that young pregnant women are at the greatest risk of malaria infection and have the highest parasite densities [ 18 , 38 , 39 ]. This may be attributed to the fact that adolescent pregnant women did not have adequate exposure to health services and did not gain a good awareness about malaria and its prevention approaches.…”
Section: Discussionsupporting
confidence: 90%
“…The odds of being infected with malaria were higher among individuals who did not use a bed net and those who used bed nets occasionally than those who used daily (p < 0.05). This finding is supported by a study conducted in Ethiopia [ 19 , 24 , 25 , 43 , 44 ] and Nigeria [ 30 ]. Insecticide-treated bed nets provide protection both to the individuals sleeping under them by deterring mosquito bites and family members by killing mosquitoes, thereby reducing the transmission of malaria parasites [ 39 ].…”
Section: Discussionsupporting
confidence: 79%
“…This finding is similar to the prevalence (7.52%) reported for Kombolcha (northeast Ethiopia) [ 41 ]. In Ethiopia, a much higher prevalence was reported in the East Shewa zone, central Ethiopia (20.5%) [ 42 ] in Hadiya zone, Sothern Ethiopia (25.8%) [ 43 ], and in North-west Ethiopia (20.8%) [ 44 ]. This difference might be due to variation in study design and setting i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, pregnant women in the first and second trimester of pregnancy were more infected than those in the third trimester. This result corroborates with studies conducted in the Republic of Ethiopia [17,18,19] who found that pregnant women in the first trimester of pregnancy had an increased risk of having malaria than women in the third trimester.…”
Section: Discussionsupporting
confidence: 91%